Challenges of the Tourism and Hospitality Industry in Business Analytics Adoption: An Article Perspective - Josephine N. Biadora; Xavier Lawrence D. Mendoza; Arianne Hyden S. Tonio (Garuda Prestasi Nusantara Consulting, 2024)
Business Analytics (BA) is increasingly used by tourism and hospitality businesses to improve customer experience, streamline operations, and boost revenue. However, the adoption of business analytics has created different challenges. A mini literature review was used in the study to identify challenges in the tourism and hospitality industries, focusing on adopting business analytics and identifying future research opportunities. The study found that the industry's growing customer data collection raises concerns about data issues, skills and resources, and organizational factors. Furthermore, addressing challenges like data management, skill gaps, and technological integration through strategic investments, research-driven insight, and ethical data practices can lead to sustainable growth and competitive advantage. Keywords: business analytics, tourism, hospitality industry, challenges, business performance